Peningkatan Keaktifan dan Prestasi Belajar Siswa SMP PGRI Sengon dalam Pembelajaran Fisika Menggunakan Metode POE - Amri Baihaqi Mashuda (Department of Physics Education, Universitas Mataram, 2019)
In the modern era, physics lessons are still one of the subjects that some students find difficult.When students feel difficult to learn, the result is a decrease in the value of physics lessons. Based on these problems, researchers try to provide solutions to overcome the difficulties students in learning physics. This research was conducted at the PGRI First Middle School in Sengon Village, Purwosari District.Improving student learning achievement can be influenced by several factors, one of which is the activity of students in the learning process of physics. On increasing learning activity students can use several methods, one of which is the POE method (Prediction, Observation, and Explanation). In this method learning is centered on students, the prediction step is predicting and thinking examples of experiments conducted by the teacher. Observation step, students conduct experiments directly and explanation step students are required to communicate in the form in sentences from the step of prediction and observation. Measuring activity with observations made by peers in the learning process, while achievements with questions given in cycles I and II. Based on the results of the research cycle I and cycle II in terms of activity and student learning achievement said to increase well. On results of these research, it can be said that physics learning using the POE method is a solution to overcome a decline in student learning achievement.